Entrepreneurship Resilience: Can Psychological Traits of Entrepreneurial Intention Support Overcoming Entrepreneurial Failure? - Zhao, Hong; Wibowo, Ardy (Frontiers in Psychology, 2021)
Entrepreneurial failure (EF) can occur due to aspects beyond the control of an entrepreneur, even if planning and calculations have been thorough. This research proposes a framework to illustrate how entrepreneurs cope with failure, based on the psychological characteristics that lead them to become entrepreneurs. Entrepreneurial self-efficacy and internal locus of controls measure the perceived learning from failure and recovery ability that can support continued entrepreneur engagement and new opportunity recognition after a failure. This study applied Partial Least Square to calculate and evaluate data from 146 respondents to an online questionnaire survey. The analysis shows that the psychological characteristics represented by entrepreneurial self-efficacy and internal locus of control can influence the willingness of entrepreneurs to learn from failure and increase their ability to recover. This can increase the willingness to continue in entrepreneurship and help them to recognize new opportunities. However, recovery ability does not support entrepreneurial self-efficacy or new opportunity recognition because the ability to recover may vary among the entrepreneurs, depending on many factors.